(3efGbH CHj GdYHGS GdqSHJjs - (3jhSa Hf jMji Hf YjSi Hf YHO GdQMef GdJGOdj, CHh GdMLGL, GdeYQha HGHf GdnqRnqjGJ,J (B627 (3g` s
(3ChdgG (B:s
(3hHYO, aEfi deG TQYJ aj JCdja UGdMi GdeZQH GdPjf LeYJge aj cJGHi GdehShe HGdJThb Edi QLGd GdJUha CTGQ Ydi LedI ef GdaVdGA Cf CPcQ ajge GdTjN GdUGdM CHG GdYHGS s
(3BNQgG (B:s
(3fSCd Gddg JYGdi GdJhajb deG ajg QVGg HLhOg hcQeg hUdi Gddg Ydi eMeO hBdg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B343s
(3Odjd eDQN GdeZQH (B- (3U (B257 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B429 s
(3eUOQ GbJfGA GdCUd (B:s
(3QhGb GdeZGQHI (B- (3GdCRgQ (B(1167) s
Keywords: (3GdJGQjNs